2021
DOI: 10.3390/ijerph181910144
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tasking during Trip Recovery and Obstacle Clearance among Young, Healthy Adults in Human Factors Research

Abstract: Trip-induced falls are extremely common in ergonomic settings. Such situations can lead to fatal or non-fatal injuries, affecting the workers’ quality of life and earning capacity. Dual tasking (DT) is a leading cause of trips and ineffective obstacle clearance among workers. DT increases their attentional demand, challenging both postural control and concurrent secondary tasks. As the human brain has limited attentional processing capacity, even young, healthy adults need to prioritize duties during DT. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several limitations of the current study include the testing of a healthy, young population who may have a lower impact due to noise and physical workload, whereas individuals with any neurological, auditory, or vestibular disorders or an elderly population may behave differently with noise and physical workload exposure [32]. Therefore, the observed results can only be generalized to the population tested.…”
Section: Limitations Future Directions and Applicationsmentioning
confidence: 96%
“…Several limitations of the current study include the testing of a healthy, young population who may have a lower impact due to noise and physical workload, whereas individuals with any neurological, auditory, or vestibular disorders or an elderly population may behave differently with noise and physical workload exposure [32]. Therefore, the observed results can only be generalized to the population tested.…”
Section: Limitations Future Directions and Applicationsmentioning
confidence: 96%
“…Stumbling over obstacles frequently occurs due to decreased toe-obstacle clearance [3] and weakened lower limb muscle power [4]; furthermore, lack of attention to obstacles is also a major factor [5,6]. Several studies examined the influence of attention on obstacle avoidance behavior by dual-task paradigm [7][8][9][10]. Lo and Chou [9] reported that the visual attention required to perform dual tasks leads to distinct modification of motor performance during obstacle crossing.…”
Section: Introductionmentioning
confidence: 99%